2022
DOI: 10.1177/02655322211063785
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of productive vocabulary tests for isiZulu, Siswati and English in South Africa

Abstract: Multilingualism in education is encouraged in South Africa, and children are expected to become bilingual and biliterate during the early primary grades. Much focus has been placed on measuring literacy in children’s first language, often the medium of instruction (MOI), and English, the language typically used as MOI from fourth grade. However, vocabulary development in African contexts is underexplored, owing to the cost of existing English standardized tests, and the comparatively fewer linguistically and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…Early Grade Reading Assessment (EGRA) instruments used to gather the word reading and reading comprehension data are available on the Department of Basic Education website at https://www.education.gov.za/Programmes/ EarlyGradeReadingStudy.aspx or on request from the authors. The Productive Vocabulary Test isiZulu/Siswati (Wilsenach et al, 2019a) and English (Wilsenach et al, 2019b) (Henrich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early Grade Reading Assessment (EGRA) instruments used to gather the word reading and reading comprehension data are available on the Department of Basic Education website at https://www.education.gov.za/Programmes/ EarlyGradeReadingStudy.aspx or on request from the authors. The Productive Vocabulary Test isiZulu/Siswati (Wilsenach et al, 2019a) and English (Wilsenach et al, 2019b) (Henrich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents the sample characteristics of children in the vocabulary study, as reported by Wilsenach and Schaefer (2022). The sample is similar to the main EGRS2 sample described previously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, they perform poorly on problems involving language (Van der Walt et al, 2008). This is especially pronounced in bilingual and multilingual learners since they develop literacy simultaneously in two languages (Cockcroft, 2016;Wilsenach and Schaefer, 2022). Such learners perform more poorly than monolingual learners who get in-depth exposure to one language (Cockcroft, 2016).…”
Section: Introductionmentioning
confidence: 99%